Effect of rubidium fluoride on grain sintering and optoelectronic properties of nanostructured cuinse2 thin films obtained by solution processing (2023)
Chalcopyrite CuInSe2 (CISe) and Cu(In, Ga)(S, Se)2 (CIGS) absorber layers, have emerged as promising alternatives in the solar cell field due to their unique properties such as power conversion efficiencies (PCEs) above 20 %, direct bandgap, and high absorption coefficient. This enables the making of high-quality PV devices with absorbers from 2 μm thick, significantly reducing the use of raw materials. Additionally, the CISe absorber layer is a desirable material for Perovskite/CIS tandem configuration with a narrow band gap at the bottom that has demonstrated PCEs close to 25 %, and potential applications in lightweight and/or flexible substrates. Recently, the addition of alkali elements such as sodium, potassium, rubidium, and cesium via post-deposition techniques (PDTs) has demonstrated an improvement in CIGS-based solar cells’ performance. In this study, 10, 20, and 30 nm thick layers of rubidium fluoride were post-deposited on CISe-films made by solution processing techniques and then selenized under a selenium-argon atmosphere to improve the CISe photoelectronic properties such as the number of charge carriers collected and grain growth, critical characteristics to ensure useful photovoltaic devices. Thus, the effect of rubidium fluorine on CISe-based solar cells was analyzed using several characterization techniques. According to the results, thin films made by an amine-thiol mixture with uniform atomic composition were obtained. The crystallinity and grain growth improved with an increase in rubidium fluoride addition. Moreover, with 10 nm of rubidium fluoride, an improvement in the lifetime of the charge carrier, photoluminescence intensity, and the number of carriers collected by the solar cells was obtained.